Benefits of dance for Parkinson’s: The music, the moves, and the company - Corinne Jola; Moa Sundström; Julia McLeod (PLoS ONE, 2022)
Dance classes designed for people with Parkinson’s are very popular and associated not only with increasing individuals’ motor control abilities but also their mood; not least by providing a social network and the enjoyment of the music. However, quantitative evidence of the benefits is inconsistent and often lacks in power. For a better understanding of the contradictory findings between participants’ felt experiences and existing quantitative findings in response to dance classes, we employed a mixed method approach that focussed on the effects of music. Participant experience of the dance class was explored by means of semi-structured interviews and gait changes were measured in a within-subjects design through the Timed Up and Go (TUG) test before and after class, with and without music. We chose the TUG test for its ecological validity, as it is a simple test that resembles movements done in class. We hypothesised that the music and the dance class would have a facilitating effect on the TUG performance. In line with existing research, we found that before class, the gait of 26 participants was significantly improved when accompanied by a soundtrack. However, after class, music did not have a significantly facilitating effect, yet gait without music significantly improved after class compared to before. We suggest that whilst the music acts as an external stimulator for movement before the dance class, after the dance class, participants have an internalised music or rhythm that supports their motor control. Thus, externally played music is of less relevance. The importance of music was further emphasised in the qualitative data alongside social themes. A better understanding of how music and dance affects Parkinson’s symptoms and what aspects make individuals ‘feel better’ will help in the design of future interventions.